2012
DOI: 10.1007/978-1-62703-050-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Population Effects and Variability

Abstract: Chemical risk assessment for human health requires a multidisciplinary approach through four steps: hazard identification and characterization, exposure assessment, and risk characterization. Hazard identification and characterization aim to identify the metabolism and elimination of the chemical (toxicokinetics) and the toxicological dose-response (toxicodynamics) and to derive a health-based guidance value for safe levels of exposure. Exposure assessment estimates human exposure as the product of the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…There is a crucial need for the development of approaches to estimate the quantitative impact of human interindividual variability in personal risk from chemical exposures (Zeise et al 2013), and with adequate human data, a number of statistical and computational tools are available to toxicologists and risk assessors (Dorne et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…There is a crucial need for the development of approaches to estimate the quantitative impact of human interindividual variability in personal risk from chemical exposures (Zeise et al 2013), and with adequate human data, a number of statistical and computational tools are available to toxicologists and risk assessors (Dorne et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, effect biomarkers have been found to be effective only when people exposed to high levels of contaminants (e.g., working with mutagenic agents), and they are difficult to use to differentiate the effects of individuals. Toxicological studies have shown that individuals' responses to chemical exposure can often vary significantly (15). Ladeira and Viegas (14) consider that such differences between individuals may be genetically mediated or caused by some environmental stressor, disease process, or other epigenetic factor.…”
Section: Human Biomonitoring the Human Biomonitoring Methodologymentioning
confidence: 99%
“…The US-EPA has discussed a number of criteria for the acceptance of PB-TK models in risk assessment: (1) the model represents the species and life stage of relevance for the specific risk assessment, (2) the model has been evaluated and peer-reviewed for transparency, adequacy of its structure and parameters, and (3) the model provides adequate simulations of the concentration of the toxic moiety (parent compound or metabolite(s)) in the target organ (or a surrogate compartment of the body), relevant exposure route(s) and relevant time-course for which the chemical would be present in that target organ/surrogate compartment (US-EPA, 2006). In the future, PB-TK models may be increasingly used, on a case by case basis depending on the purpose of the risk assessment and data availability, as more generic predictive tools become available (Conolly et al, 2005;US-EPA, 2007;EFSA, 2008;Dorne et al, 2012). In the future, PB-TK models may be increasingly used, on a case by case basis depending on the purpose of the risk assessment and data availability, as more generic predictive tools become available (Conolly et al, 2005;US-EPA, 2007;EFSA, 2008;Dorne et al, 2012).…”
Section: Principlesmentioning
confidence: 99%
“…In terms of validation, 4 key aspects to be reviewed have been identified 1. model purpose and structure, 2. mathematical representation, 3. calibration of the parameter estimations, and 4. computer implementation of the model. In the future, PB-TK models may be increasingly used, on a case by case basis depending on the purpose of the risk assessment and data availability, as more generic predictive tools become available (Conolly et al, 2005;US-EPA, 2007;EFSA, 2008;Dorne et al, 2012).…”
Section: Principlesmentioning
confidence: 99%